2010
DOI: 10.1016/j.tsf.2009.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Si1−xGex growth using Si3H8 by low temperature chemical vapor deposition

Abstract: Low temperature epitaxial growth of group-IV alloys is a key process step to realize the advanced Si-based devices. In order to keep high growth rate below 600 °C, trisilane (Si3H8) was used for their growth as an alternative Si precursor gas. Then, we compared the use of Si3H8 versus SiH4 for Si1-xGex growth in H2 and N2 as carrier gas by low temperature chemical vapor deposition. By using Si3H8 and controlling GeH4 flow rate, Si1-xGex growth with high growth rate and wide range of Ge concentration has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…1b͒. 13 This growth enhancement is caused by the faster H desorption from Ge sites due to the weaker Ge-H bond 14 in case there is no oversaturation with H from an H 2 environment. Based on these considerations, a deposition test was set up based on SiH 4 in N 2 carrier gas flow in the temperature range of 500-575°C.…”
Section: Si Passivation With a Sih 4 -Based Deposition Processmentioning
confidence: 99%
“…1b͒. 13 This growth enhancement is caused by the faster H desorption from Ge sites due to the weaker Ge-H bond 14 in case there is no oversaturation with H from an H 2 environment. Based on these considerations, a deposition test was set up based on SiH 4 in N 2 carrier gas flow in the temperature range of 500-575°C.…”
Section: Si Passivation With a Sih 4 -Based Deposition Processmentioning
confidence: 99%
“…Recent work at 500ºC has however shown that the growth rate of Si from SiH 4 , even in N 2 , is quasi zero, but the Si equivalent deposition rate in SiGe alloys with a Ge content of ~ 20 % (with the addition of GeH 4 ), also at 500ºC, reaches a value of 0.03 ML/sec in H 2 and shoots up to ~ 0.4 ML/sec in N 2 , see Fig. 1 right pane (15). This growth enhancement is caused by the faster H desorption from Ge sites, due to the weaker Ge-H bond (16).…”
Section: Epitaxial Growth Of the Si Capping Layer From Sihmentioning
confidence: 96%
“…However, it is plagued by relatively slow Growth Rates (GR) at low temperatures, as confirmed by the following. Meanwhile, hydrogenated silicon precursors (such as silane (SiH4) [5], disilane (Si2H6) [6][7][8][9], trisilane (Si3H8) [10][11][12][13] or tetrasilane (Si4H10) [14][15]), yield significantly higher Si and SiGe growth rates at low temperatures. Such precursors are intrinsically non selective versus dielectric masking materials, but this difficulty can be overcome with advanced (Cyclic) Deposition / Etch processes [6], [16][17][18][19].…”
Section: -Introductionmentioning
confidence: 99%